Respuesta :

Answer:

x = 3

x + 3 = 6

√45

Step-by-step explanation:

the general theorem is

a^2 + b^2 = c^2

Givens

a = x

b = x + 3

c = √45

Solution

x^2 + (x + 3)^2 = (√45)^2          Substitute

x^2 + x^2 + 6x + 9 = 45             Expand the brackets. Square √45  

2x^2 + 6x + 9 = 45                    Subtract 45 from both sides

2x^2 + 6x - 36 = 0                     Divide by 2

x^2 + 3x - 18 = 0                        Factor

(x + 6)(x - 3) = 0                         x+ 6 has no meaning in the real world.

x - 3 = 0

x = 3                                          

Answer

a) 3

b) 6

c) √45

ACCESS MORE